2018
DOI: 10.1371/journal.pone.0209177
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic (PK/PD) evaluation of tulathromycin against Haemophilus parasuis in an experimental neutropenic guinea pig model

Abstract: The objective of the study was to develop an ex-vivo PK/PD model of intramuscular (IM) administration of tulathromycin and to test its efficacy against Haemophilus parasuis (H. parasuis) infection in intraperitoneal-inoculated neutropenic guinea pigs. The pharmacokinetics (PKs) of tulathromycin at doses of 1 and 10 mg/kg in H. parasuis-infected neutropenic guinea pig were studied by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). In vitro minimum inhibitory concentration (MIC), mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…However, the electrophoretic mobility of this band (within the 130–180 KDa gel region) was identical to that identified as GH36 (Uniprot code: G2TQE8, Additional file 1 : Table S1) thus indicating that the enzymatic activity revealed by zymography, can be ascribed to the same protein. Besides our experimental evidences, the extracellular localization of the α-galactosidase has been previously described for another closely related B. coagulans strain [ 31 , 45 ] as well as for other soil microorganisms [ 46 ] and for Bacillus megaterium [ 47 ]. It is known that galactomannans are present in seeds of bean and, in general, RFOs (raffinose, stachyose, and verbascose) that contain α 1–6-linked galactose units, are particularly abundant in these legumes [ 9 ].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…However, the electrophoretic mobility of this band (within the 130–180 KDa gel region) was identical to that identified as GH36 (Uniprot code: G2TQE8, Additional file 1 : Table S1) thus indicating that the enzymatic activity revealed by zymography, can be ascribed to the same protein. Besides our experimental evidences, the extracellular localization of the α-galactosidase has been previously described for another closely related B. coagulans strain [ 31 , 45 ] as well as for other soil microorganisms [ 46 ] and for Bacillus megaterium [ 47 ]. It is known that galactomannans are present in seeds of bean and, in general, RFOs (raffinose, stachyose, and verbascose) that contain α 1–6-linked galactose units, are particularly abundant in these legumes [ 9 ].…”
Section: Resultssupporting
confidence: 58%
“…A thoroughly biochemical characterization of a closely related recombinant α-galactosidase from B. coagulans ATCC 7050 (identity percentage 97.4%) has been recently published [ 31 ]. Therefore, we focused on the study of the β-galactosidase enzyme, since there is no evidence about the ability of β-galactosidases from other B. coagulans strains to produce GOS upon transglycosylation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The same antibiotic has different types of action on different bacteria [35]. A number of studies have shown that when macrolide antibiotics are concentration-dependent, the best PK/PD parameter is AUC/MIC [36][37][38][39]. The main reasons for the high correlation between AUC 96h /MIC and C max /MIC in this experiment are the lack of fitting analysis data and the relatively close trend.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, the values of the PK/PD indexes are routinely given in terms of free concentrations, not total concentration. In the previous study, the free fraction (fu) of tulathromycin in guinea pig serum was 0.56-0.74 (41). Thus, the PK/PD index, fAUC/MIC (0-72 h) corresponding to 1-, 2-, 3-, and 4-log 10 were 174.75, 259.99, 339.24, 422.68 h, respectively, and fAUC/MIC (0-168 h) corresponding to 1-, 2-, 3-, and 4log 10 were 237.94, 359.13, 473.51, 595.99 h, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…In veterinary medicine, tulathromycin is highly effective against respiratory diseases in cattle, swine, horses, and goats (32)(33)(34)(35)(36)(37). Recently, researchers used serum or tissue cage fluid to investigate the pharmacokinetics and ex vivo pharmacodynamic activity of tulathromycin against Pasteurella multocida (38) and Streptococcus suis (39) in pigs, and against Mannheimia haemolytica and Pasteurella multocida (40) in cattle, and ex-vivo PK/PD model of tulathromycin against H. parasuis in intraperitoneal-inoculated neutropenic guinea pigs (41). However, no study has reported on in vivo PK/PD profiles of tulathromycin in pigs.…”
Section: Introductionmentioning
confidence: 99%